Semiotic Analysis of Islamic Communication in The Film "Ajarkan Aku Aceh" for Tourism Promotion - Asmaunizar; Abdurrahman; Winda Kustiawan (DAWUH : Islamic Communication Journal, 2026)
This research analyzes the implementation of Islamic communication semiotics in the film "Ajarkan Aku Aceh" as a medium for promoting sharia-based tourism. Using a qualitative approach with Roland Barthes' semiotic analysis, the research examines the construction of denotative, connotative, and mythological meanings in the visual representation of Aceh's tourism. The results show that the film successfully integrated Islamic values with destination promotion strategies by transforming visual elements into symbols of spirituality and community hospitality. The construction of the "Serambi Mekkah" mythology creates a unique selling proposition that distinguishes Aceh from other destinations. The film constructs a holistic tourism paradigm that emphasizes educational, spiritual, and cultural dimensions, creating sacred geography and emotional connections with the audience. The findings reveal the potential of film as an effective contextual preaching instrument in the digital era, contributing theoretically to the development of an Islamic communication model for tourism marketing based on religious values.